2020
DOI: 10.1111/jgs.16648
|View full text |Cite
|
Sign up to set email alerts
|

Family Caregiving at the End of Life and Hospice Use: A National Study of Medicare Beneficiaries

Abstract: BACKGROUND/OBJECTIVES: Hospice care confers well-documented benefits to patients and their families, but it is underutilized. One potential reason is inadequate family support to make end-of-life decisions and care for older adults on hospice at home. We assessed the association between amount of family support and hospice use among a population of decedents and among specific illness types. DESIGN: Prospective cohort study using the National Health and Aging Trends Study waves 2011 to 2017, linked to Medicare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 44 publications
0
31
0
Order By: Relevance
“…The same study found that 72% of family caregivers experienced relief when the person with Alzheimer's or another dementia died 445 . In the last 12 months of life, people with dementia relied on more hours of family care (64.5 hours per week) than people with cancer (39.3 hours per week) 446 . In addition, caregivers living with a family member with dementia pay for 64% of total care costs incurred during their family member's last seven years of life 447 …”
Section: Caregivingmentioning
confidence: 95%
“…The same study found that 72% of family caregivers experienced relief when the person with Alzheimer's or another dementia died 445 . In the last 12 months of life, people with dementia relied on more hours of family care (64.5 hours per week) than people with cancer (39.3 hours per week) 446 . In addition, caregivers living with a family member with dementia pay for 64% of total care costs incurred during their family member's last seven years of life 447 …”
Section: Caregivingmentioning
confidence: 95%
“…482 • In the last 12 months of life, people with dementia relied on more hours of family care (64.5 hours per week) than people with cancer (39.3 hours per week). 483 In addition, caregivers living with a family member with dementia pay for 64% of total care costs incurred during their family members' last seven years of life. 484…”
Section: Burden and Stressmentioning
confidence: 99%
“…Given the importance of the informal social network for hospice family caregivers and the potential for stress/support ambivalence within these networks, examining both in the context of EOL caregiving may provide important insight into how the need to balance stress and support affects caregivers' outcomes. Despite this, the composition of hospice family caregivers' informal social networks and the potential for stress/support ambivalence within relationships with network members have received little attention in the research literature (Jacobs et al, 2016;Kumar et al, 2020;Roth, 2020a).…”
Section: Potential For Stress and Support Ambivalence Within Support Relationshipsmentioning
confidence: 99%